\begin{align} \frac{d^4y}{dx^4}\;+\;\sin(y^m)\;=0 \end{align}
\begin{align} \Rightarrow y^{m\;'}+\;\sin(y^m)\;=0 \end{align}
The highest order derivative present in the differential equation is ym '. Therefore, its order is four.
The given differential equation is not a polynomial equation in its derivatives. Hence, its degree is not defined.
yn + 2y' + siny = 0
The highest order derivative present in the differential equation is yn. Therefore, its order is two.
This is a polynomial equation in yn and y' and the highest power raised to yn is one. Hence, its degree is one.
\begin{align}\left(\frac{d^2y}{dx^2}\right)^3\;+ \left(\frac{dy}{dx}\right)^2+\;sin\left(\frac{dy}{dx}\right)\;+ 1=\;0\end{align}
The given differential equation is not a polynomial equation in its derivatives. Therefore, its degree is not defined.
Hence, the correct answer is D.
\begin{align}2x^2\frac{d^2y}{dx^2}\;- \;3\frac{dy}{dx}\;+ y=\;0\end{align}
The highest order derivative present in the given differential equation is
\begin{align}\frac{d^2y}{dx^2}\end{align}
Therefore, its order is two.
Hence, the correct answer is A.
The given differential equation is:
y' + 5y = 0
The highest order derivative present in the differential equation isy'. Therefore, its order is one.
It is a polynomial equation in y'. The highest power raised to y' is 1. Hence, its degree is one.
\begin{align}\left(\frac{ds}{dt}\right)^4\;+\;3s\frac{d^2s}{dt^2}\;=\;0\end{align}
The highest order derivative present in the given differential equation is\begin{align}\frac{d^2s}{dt^2}.\end{align}
Therefore, its order is two. It is a polynomial equation in
\begin{align}\frac{d^2s}{dt^2} and \frac{ds}{dt}.\end{align}
The power raised to is 1. \begin{align} \frac{d^2s}{dt^2} \end{align}
\begin{align}\left(\frac{d^2y}{dx^2}\right)^2\;+\;cos\left(\frac{dy}{dx}\right)\;=\;0\end{align}
The highest order derivative present in the given differential equation is \begin{align}\frac{d^2y}{dx^2}.\end{align}
Therefore, its order is 2. The given differential equation is not a polynomial equation in its derivatives.
Hence, its degree is not defined.
\begin{align}\frac{d^2y}{dx^2}=\cos3x + sin3x\end{align}
\begin{align}\Rightarrow\frac{d^2y}{dx^2} - \cos3x - sin3x = 0\end{align}
The highest order derivative present in the differential equation is\begin{align}\frac{d^2y}{dx^2}.\end{align}
Therefore, its order is two.It is a polynomial equation in \begin{align}\frac{d^2y}{dx^2}\end{align}
and the power raised to is 1.
\begin{align}\frac{d^2y}{dx^2}\end{align}
Hence, its degree is one.
(ym)2 + (yn)3 + (y')4 + y5 =0
The highest order derivative present in the differential equation isym. Therefore, its order is three.
The given differential equation is a polynomial equation in ym , yn , y'.
The highest power raised to ym is 2. Hence, its degree is 2.
The highest order derivative present in the differential equation is ym. Therefore, its order is three.
It is a polynomial equation in ym , yn and y' . The highest power raised to ym is 1. Hence, its degree is 1.
y' + y =ex
y' + y - ex =0
The highest order derivative present in the differential equation is y'. Therefore, its order is one.
The given differential equation is a polynomial equation in y' and the highest power raised to y' is one. Hence, its degree is one.
yn + (y')2 + 2y =0
The highest order derivative present in the differential equation is yn. Therefore, its order is two.
The given differential equation is a polynomial equation in yn and y' and the highest power raised to yn is one.
Hence, its degree is one.
y = ex +1
Differentiating both sides of this equation with respect to x, we get:
\begin{align}\frac{dy}{dx}=\frac{d}{dx}(e^x + 1)\end{align}
=> y' = ex ...(1)
Now, differentiating equation (1) with respect to x, we get:
\begin{align}\frac{d}{dx}(y^{'})=\frac{d}{dx}(e^x)\end{align}
=> y'' = ex
Substituting the values of y' and y'' in the given differential equation, we get the L.H.S. as:
y'' - y' = ex - ex = 0 = R.H.S.
Thus, the given function is the solution of the corresponding differential equation.
y = x2 + 2x + C
Differentiating both sides of this equation with respect to x, we get:
\begin{align}y^{'}=\frac{d}{dx}(x^2 + 2x + C)\end{align}
=> y' = 2x + 2
Substituting the value of y' in the given differential equation, we get:
L.H.S. = y' - 2x - 2 = 2x + 2 - 2x - 2 = 0 = R.H.S.
Hence, the given function is the solution of the corresponding differential equation.
y = cosx + C
Differentiating both sides of this equation with respect to x, we get:
\begin{align}y^{'}=\frac{d}{dx}(cosx + C)\end{align}
=> y' = - sinx
Substituting the value of y' in the given differential equation, we get:
L.H.S. = y' + sinx = - sinx + sinx = 0 = R.H.S.
Hence, the given function is the solution of the corresponding differential equation.
\begin{align} y= \sqrt{1+x^2}\end{align}
Differentiating both sides of the equation with respect to x, we get:
\begin{align} y^{'}=\frac{d}{dx}\left(\sqrt{1+x^2} \right)\end{align}
\begin{align} y^{'}=\frac{1}{2\sqrt{1+x^2}}\frac{d}{dx}\left(1+x^2\right)\end{align}
\begin{align} y^{'}=\frac{2x}{2\sqrt{1+x^2}}\end{align}
\begin{align} y^{'}=\frac{x}{\sqrt{1+x^2}}\end{align}
\begin{align}\Rightarrow y^{'}=\frac{x}{\sqrt{1+x^2}}\frac{\sqrt{1+x^2}}{\sqrt{1+x^2}}\end{align}
\begin{align}\Rightarrow y^{'}=\frac{x}{1+x^2}{\sqrt{1+x^2}}\end{align}
\begin{align}\Rightarrow y^{'}=\frac{x}{1+x^2}{y}\end{align}
\begin{align}\Rightarrow y^{'}=\frac{xy}{1+x^2}\end{align}
∴ L.H.S. = R.H.S.
Hence, the given function is the solution of the corresponding differential equation.
y = Ax
Differentiating both sides with respect to x, we get:
\begin{align}y^{'}=\frac{d}{dx}(Ax)\end{align}
⇒ y ' = A
Substituting the value of y' in the given differential equation, we get:
L.H.S. = xy' = xA = Ax = y = R.H.S.
Hence, the given function is the solution of the corresponding differential equation.
y= x.sinx
Differentiating both sides of this equation with respect to x, we get:
\begin{align} y^{'} =\frac{d}{dx}\left(x.sinx\right)\end{align}
\begin{align}\Rightarrow y^{'} =sinx. \frac{d}{dx}\left(x\right)+ x. \frac{d}{dx}\left(sinx\right)\end{align}
\begin{align} \Rightarrow y^{'} =sinx + x.cosx\end{align}
Differentiating both sides of this equation with respect to x, we get:
L.H.S. =xy' = x(sinx + xcosx)
\begin{align} =x.sinx + x^2.cosx\end{align}
\begin{align} =y + x^2.\sqrt{1-sin^2x}\end{align}
\begin{align} =y + x^2.\sqrt{1-\left(\frac{y}{x}\right)^2}\end{align}
\begin{align} =y + x^2.\sqrt{\frac{x^2-y^2}{x^2}}\end{align}
\begin{align} =y + x.\sqrt{x^2-y^2}\end{align}
R.H.S.